Transplant-Ineligible Symptomatic but Indolent Multiple Myeloma Shows Better Prognosis with Conventional Agents - Nakaya, Aya (Case Rep Oncol, 2017)
The survival of multiple myeloma patients has improved significantly over the last several decades. However, the median overall survival of these patients remains less than 5 years. In this report, we discuss 4 cases of multiple myeloma patients that showed long survival. Interestingly, these patients had severe organ damage at diagnosis, used only conventional agents, and did not always show deep response. Although current guidelines recommend novel agents to achieve deep response, the current cases suggest that some multiple myeloma patients may not need intensive treatment. Here, we discuss 4 cases of symptomatic but indolent transplant-ineligible myeloma.